A Lasso‐Inspired Bicyclic Peptide: Synthesis, Structure and Properties. Issue 72 (4th December 2018) - Martin‐Gómez, Helena; Albericio, Fernando; Tulla‐Puche, Judit
Abstract: The chemical synthesis of a bicycle inspired by the natural lasso peptide sungsanpin using a combination of solid‐phase and in‐solution chemistries is described. The bicyclic‐derived topoisomer was designed by introducing a covalent linkage between the ring and the loop, which allowed the tying of these two parts of the peptide, rendering the bicyclic structure. Several structural techniques, such as MS fragmentation, ion‐mobility and NMR spectroscopic analysis were used to characterize the bicycle. Ion‐mobility spectroscopy studies revealed that it showed lasso‐like behavior. Its 3D structure was predicted on the basis of the NMR restraints. In addition, the high proteolytic and thermal stability of the bicycle potentially make it a suitable scaffold for epitope grafting. Abstract : A panoply of protecting groups : The proper selection of a large number of protecting groups together with the combination of solid‐phase/solution chemistry hybrid approach, allowed the chemical synthesis of a bicyclic peptide inspired by the natural lasso peptide sungsanpin (see figure).